2023
DOI: 10.3390/pharmaceutics15020627
|View full text |Cite
|
Sign up to set email alerts
|

A Gelatin Methacrylate-Based Hydrogel as a Potential Bioink for 3D Bioprinting and Neuronal Differentiation

Abstract: Neuronal loss is the ultimate pathophysiologic event in central nervous system (CNS) diseases and replacing these neurons is one of the most significant challenges in regenerative medicine. Providing a suitable microenvironment for new neuron engraftment, proliferation, and synapse formation is a primary goal for 3D bioprinting. Among the various biomaterials, gelatin methacrylate (GelMA) stands out due to its Arg-Gly-Asp (RGD) domains, which assure its biocompatibility and degradation under physiological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Furthermore, it could provide a suitable environment for the differentiation and generation of mouse astrocytes (Figure 6j). 89 Recent studies have shown that an increasing number of experiments have successfully integrated neural stem cells directly into bioprinted scaffolds without detrimental effects on cell survival and activity. Moreover, these studies have demonstrated the beneficial role of bioprinted scaffolds in The development of bioink and scaffolds is built upon in vitro experiments, aiming to promote neural cell differentiation and construct neural tissue.…”
Section: Neuralmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it could provide a suitable environment for the differentiation and generation of mouse astrocytes (Figure 6j). 89 Recent studies have shown that an increasing number of experiments have successfully integrated neural stem cells directly into bioprinted scaffolds without detrimental effects on cell survival and activity. Moreover, these studies have demonstrated the beneficial role of bioprinted scaffolds in The development of bioink and scaffolds is built upon in vitro experiments, aiming to promote neural cell differentiation and construct neural tissue.…”
Section: Neuralmentioning
confidence: 99%
“…The coagulated bioink, as shown in Figure i, supported the idea that human neural stem cells were successfully differentiated in immature neurons. Furthermore, it could provide a suitable environment for the differentiation and generation of mouse astrocytes (Figure j) …”
Section: Bioinks For 3d Bioprinting Of Tissues and Organsmentioning
confidence: 99%
See 3 more Smart Citations